Modular manufacturing and supplier relations: A survey of practices in the Turkish automotive supplier industry - (:unkn) unknown (PICMET, 2007)
During the last fifteen years the structural changes of the automotive industry have modified the technology and the business organization of the large automakers and their suppliers in many ways. This paper analyzes the main results of a survey to 63 automotive suppliers in the Turkish automotive supplier industry. Nearly half of the companies cooperate with customers, suppliers, and technological centers to improve their production processes but only three companies cooperate with their customers in component development and design which indicates an under involvement of the surveyed companies with the automotive manufacturers. However, these organizational and technological changes in the automakers have also influenced their suppliers. The auto manufacturers have increasingly externalized their purchases and their component design to first-tier suppliers, diffusing modular production practices throughout the supply chain [1]. Therefore, more recent studies have focused on the auto supplier industry and its relationship with the automakers. In Turkey, these studies are very scarce 121 and so this paper wishes to contribute to this research area, giving empirical evidence of some modular production practices in the supplier automotive industry of an Turkish region.
Keywords: MASS CUSTOMIZATION; STRATEGIC FLEXIBILITY; PRODUCT DEVELOPMENT; DESIGN; CHAIN